Conceptual model for retail distribution in nanostores: the case of the southwest of Barranquilla, Colombia (2023)
This article designs a conceptual model for the procurement and distribution processes in nanostores in the southwest of Barranquilla, Colombia considering 256 nanostores. The data collection involved identifying the nanostores through a visit to the area and creating a data collection instrument with specific questions covering various variables. As a result of the model, the procurement process comprises stages such as ordering, order processing, preparation and dispatch, distribution, payment, return, and after-sales. The findings show that nanostores primarily use indirect distribution channels, establishing relationships with suppliers and placing orders directly or through sales agents. Based on the research findings, the article suggests implementing digital marketing platforms to facilitate order placement and delivery for nanostore owners, reducing their transportation costs and improving the condition of products received. This study contributes to understanding procurement and distribution dynamics in nanostores, providing valuable insights for nanostore owners, policymakers, and researchers, improving the operations and competitiveness of nanostores, benefiting both the local economy and the broader retail sector.